Liability Of A Carrier Based On Sea Carriage Document In Indonesia (A Way Forward To E-Document) - Irma Rachmawati Maruf; T. Subarsyah; Ahmad Ridwan Tentowi; Valda Zahira Sidqy (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2020)
Maritime Document tin Indonesian law refers to the regulations of the Indonesian Commercial Code and International Conventions such as The Hague Rules in 1928 and The Hague Visby Rules of 1968. As an essential document in international trade, the conventions are also very influential. One of the latest conventions is the U.N. Convention on Contract for the International Carriage of Goods Wholly or Partly by Sea, which was signed in Rotterdam in 2009 (Rotterdam Rules).  The problem arises when until now Indonesian Government is not a party nor ratified of those Convention and for the e-document Indonesia only apply e-Bill of Lading (e-B/L).  The research method is a legal analysis of the key provision of the relevant law upon Maritime Law.  The findings indicated that   Maritime Documents in Indonesia, are divided into charter agreement and bill of lading agreement. It also find that E-B/L Bill is not suitable   in Common nor Civil law jurisdiction.